Understanding The Role of E-Wom Towards The Intention of The Millenial Generation to Visit Tourism Village - Bhuana, Tri Yana; Suardana, IB Raka (Jurnal Penelitian Pariwisata, 2022)
The Bali Provincial Government had focused on tourist villages even before regional regulation 5 of 2020 was issued. The millennial generation is a generation that grows and develops along with technological advances. The millennial generation, or Gen-Y, becomes the best customer when promoting local wisdom and tourism village traditions through social media. The purpose of this study was to determine the effect of E-WOM or social media reviews on the intentions or intentions of the millennial generation in visiting tourist villages. This study uses quantitative methods and the millennial generation in Bali as the research sample. There are 101 online questionnaires filled out using google forms, but only 88 questionnaires meet the requirements. This study found that E-WOM or social media reviews affect the variables in the planned behavior theory. In the view of planned behavior, the subjective norm variable is the variable most influenced by E-WOM. Therefore, tourism village entrepreneurs targeting the millennial generation must start using social media and influencers and create trending topics so that information can easily reach the millennial generation. Keywords: The Role of E-Wom, The Intention of The Millenial Generation, Visit Tourism Village